Cutting edge advertising how to create the world's best print for brands in the 21st century - Aitchison, Jim (Pearson Education South Asia Pte Ltd, 2004)
"Reprinted ten times in four years and now revised and updated, this classic book is still the definitive step-by-step guide to creating cutting edge print ads. It covers everything from how advertising works, how brand-building methodologies are changing, how to get an idea, and how copy and art should be crafted."--Book jacket.